UM AMBIENTE SIG PARA MODELAGEM INTEGRADA DA QUALIDADE DA ÁGUA UTILIZANDO QUAL2E - Zeilhofer, Peter Zeilhofer; Lima, Eliana B. R.; Santos, Felipe M.; Rigo Júnior, Luís O. (Caminhos de Geografia, 2003)
This paper describes the integration of the QUAL2E model for water quality simulation in the GIS/DBMS environment of the "Integrated Monitoring System of the Cuiabá River Watershed" (SIBAC). Programmed database modules prepare data tables for an interactive QUAL2E data entry, executed by the SIBAC GIS-Environment. Modified ArcView/Avenue (ESRI) scripts, partially based on the BASINS application (USEPA 1998), allow the automated model calibration and visualization of modeling results in the GIS environment. Database and GIS tools created for evaluation of the Cuiabá watershed in Mato Grosso, Central Brazil, are appropriated for application in other river basins. Key words: GIS, water quality modelling, QUAL2E